PERBEDAAN KEMAMPUAN PENALARAN MATEMATIS MENGGUNAKAN MODEL KOOPERATIF TIPE THE POWER OF TWO AND FOUR DENGAN COOPERATIVE SCRIPT DITINJAU DARI SELF EFFICACY - Rahayu; Ade Susanti (Pendidikan Matematika | STKIP YM Bangko, 2020)
This study aims to describe the differences in mathematical reasoning abilities in terms of self efficacy using the power of two and four type of cooperative learning models with cooperative script learning models. The research method used was an experimental method with a quantitative approach using a 2 x 3 factorial design with a class population of VIII students totaling 4 classes. The sampling technique uses Simple Random Sampling, class VIII B as the experimental class 1 and class VIII C as the experimental class 2, and the two classes are grouped based on their self efficacy. Data collection using test techniques to variable mathematical reasoning abilities and questionnaires for self-efficacy. The results of the analysis show that hypotheses 1 and 3 obtained Zh <Zt, hypotheses 2 and 4 obtained Uh <Ut and hypothesis 5 obtained Fh < Ft, it can be concluded: the students' mathematical reasoning ability skills are not different either overall or with high, medium and low self efficacy using the power of two and four cooperative learning models with cooperative scripts. There is no interaction between self efficacy with cooperative models of the power of two and four types and cooperative scripts in influencing mathematical reasoning abilities.